2021
DOI: 10.1155/2021/8453439
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Exit Advance Guide Signs on the Trajectory and Speed of Passenger Cars in Highway Tunnels

Abstract: The driving behavior in highway tunnels is more complicated than that in regular roadbed sections because the former is usually affected by black and white hole effects, tunnel clearance, and bad illumination. Unfortunately, the current Chinese criteria and the Uniform Traffic Control Equipment Manual (MUTCD) 2009 guidelines provide no clear method for setting exit advance guide signs in highway tunnels. Hence, a driving simulator-based experiment was conducted in the current study to analyze the effects of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…It can be seen in Figure 10(c) that when exit advance guide signs are set in the tunnel, the MLCD of the off-ramp vehicle is significantly lower, and the starting points of lane changing are earlier. is is because the driver has certain psychological expectations after receiving the warning information in the tunnel, and prepares for lane changing as soon as possible after driving out of it, which is similar to the conclusion of Shang [47].…”
Section: Traffic Condition Factorsmentioning
confidence: 84%
See 1 more Smart Citation
“…It can be seen in Figure 10(c) that when exit advance guide signs are set in the tunnel, the MLCD of the off-ramp vehicle is significantly lower, and the starting points of lane changing are earlier. is is because the driver has certain psychological expectations after receiving the warning information in the tunnel, and prepares for lane changing as soon as possible after driving out of it, which is similar to the conclusion of Shang [47].…”
Section: Traffic Condition Factorsmentioning
confidence: 84%
“…A deceleration lane and a lane-changing area are set inside the tunnel so that the off-ramp vehicle completes the lane change before leaving the tunnel. (3) Set the separated exit advance guide sign at the tunnel exit or before the tunnel entrance, and give the driver some psychological expectations [47]. (4) Shading sheds can be set outside the tunnel exit to reduce the influence of "light adaptation" on lane-changing behavior.…”
Section: Improving Methodsmentioning
confidence: 99%
“…Lu et al ( 27 ) and Shang et al ( 28 ) suggested distinct advance guidance signs for the location and distance of the tunnel exit, and tested the safety efficacy of signs with varying heights, widths, and spacing depending on drivers’ visual characteristics. In addition, they also compared and analyzed the differences in visual recognition between drivers who were familiar and unfamiliar with different advance guide signs, and they discovered that advance guide signs placed on the left side wall of highway tunnels are more effective than those placed on the right side wall ( 29 ). Hu et al ( 30 ) conducted research to investigate the connection between the characteristics of contour design inside the highway tunnel and the dimensions of the guide signs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Miller [ 25 ] evaluated stress as drivers traversed along an interstate route that included tunnel and non-tunnel segments, as well as a 75-m transition period before the tunnels. Shang [ 26 , 27 ] proposed a method to set exit advance guide signs in highway tunnels, and evaluated their influence on the trajectories and speeds of passenger cars. Zhu [ 28 ] evaluated the effectiveness of three types of speed reduction markings (SRMs) in tunnel entrance and exit zones through a driving simulation experiment, and found that SRMs are necessarily implemented in the highway tunnel entrance and exit zones.…”
Section: Literature Reviewmentioning
confidence: 99%